Cover Crops, Fertilizer Nitrogen Rates, and Economic Return of Grain Sorghum. (1st January 2016) - Mahama, George Y.; Prasad, P. V. Vara; Roozeboom, Kraig L.; Nippert, Jesse B.; Rice, Charles W.
Abstract : Leguminous cover crop systems have been envisaged as a critical component of sustainable agriculture because of their potential to increase soil productivity by cycling C and N in agricultural systems. Our objectives were to: (i) determine the effects of including summer cover crops and N rates in the cropping system on the growth and yield of the succeeding grain sorghum [ Sorghum bicolor (L.) Moench] crop, (ii) calculate the N fertilizer replacement value (NFRV) and evaluate economic returns, and (iii) determine the most cost‐effective cropping system. Field experiments were conducted for two seasons in Kansas. Leguminous summer cover crops and double‐cropped soybean [ Glycine max (L.) Merr.] residues improved soil N availability; N was subsequently used by the succeeding crop. Across years and cropping systems, the mean increases in grain yield as a result of including cowpea [ Vigna unguiculata (L.) Walp.], pigeonpea [ Cajanus cajan (L.) Millsp.], sunn hemp ( Crotalaria juncea L.), double‐cropped soybean, and double‐cropped grain sorghum in the rotation compared with a fallow system with 0 kg N ha −1 were 56, 62, 43, 32, and 3%, respectively, and NFRVs across the years were 53, 64, 36, 27, and –3 kg N ha −1, respectively. Across years, grain sorghum in a double‐cropped soybean system and a fallow system with 90 kg N ha −1 gave profitable economic net returns. We conclude that including leguminous cover crops in a cropping system has the potential to reduce N requirements and improve the N availability and grain yield of the succeeding grain sorghum crop.